(untitled) (Marketing Journal, 2026)
This article examines the theoretical and conceptual foundations for improving strategic management in higher education institutions (HEIs) through the formation of № 1 -SON YANVA R, 202 6-YIL 16 sustainable competitive advantages. Based on a narrative literature review of 30 academic sources indexed in the Scopus and Web of Science databases for the period 2012 –2022, the concepts of competition, competitiveness, and sustainable competitive advanta ge are analyzed. The study explores key thematic areas, sources and types of competition, their positive and negative effects, improvement strategies, and conceptual linkages. The conclusions are presented in a logically coherent manner, with theoretical f oundations refined in the context of developing countries, including Central Asia. The article does not employ econometric analysis and is based solely on a theoretical and conceptual approach.